O brzmieniu i tłumaczeniu kanonu 33. synodu w Elwirze – najstarszego oficjalnego tekstu Kościoła o celibacie duchowieństwa - Lewandowicz, Janusz (Vox Patrum, 2013)
This article represents an attempt to expound the meaning of 33rd canon of the Council of Elvira (circa 306 A.D.), based on historical and grammatical criteria, in reference to doubts related to the linguistic understanding of the text. The author argues that the traditional interpretation of the canon as a prescription prohibiting those who have received major orders (i.e. deacons, presbyters and bishops) having marital relationship is justified (as opposed to authors who agree with the opinion presented by Maurice Meigne). This, in turn, recognises the authenticity of the text as an integral part of the entire collection of the canons of the Council of Elvira. This paper, while presenting a version of the translation of the canon, proposes also some modifications on punctuation marks, which allows the extraction of the full meaning of the text.